Is there a right to education in Nigeria? appraising the right to basic education in Nigeria (2018)
The right to education is one of the fundamental rights recognized and guaranteed in both international and regional instruments that Nigeria is a signatory to. This right is described categorically in the 1999 Constitution of the Federal Republic of Nigeria as a non-justiciable right by virtue of Section 6(6). This right is also recognized in the Child Rights Act 2003 and the Universal Basic Education Act 2004. Against this background, this article discusses the right to education as a specie of human rights. It adopts a desk review of relevant literature and case law to expatiate on the right to education as a fundamental human right. It leans on the theory of rights to argue that the right to education is a human right which is enforceable via the instrumentality of law and the institution. In doing so, it draws inferences from international legal instruments which advocate for the right to education as a human right. It then concludes that though the Nigerian 1999 Constitution as amended does not recognize the right to education as a justiciable right, however with the enactment of the Universal Basic Education Act in 2004, and by judicial activism via the pronouncement of the Nigerian courts, the right to education is now regarded as an enforceable fundamental human right in Nigeria